Design complexes calixarenes with fullerenes c60 - Михайленко, О.В.; Іванов, С.В.; Струнгар, А.В. (Proceedings of National Aviation University, 2006)
There has been investigated the impact of the nature of substitutes upon the thermodynamic and kinetic stability of “guest-host” complexes between a number of calix[4]arene derivatives and the С60 fullerene by the ММ+ method. It has been established that the availability of branched alkyl or aryl groups in 4-position of a calixarene nucleus increases the system stability. There has been also investigated the influence of the substitute’s nature in the lower ring of a calixarene upon its conformation stability and complexing ability.